2020
DOI: 10.1002/jor.24607
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin‐loaded sustained‐release hydrogel graft provides accelerated bone formation: An experimental rat study

Abstract: Restoration of the lost bone volume is one of the most deliberate issues in dentistry. Sustained‐release microspherical oxytocin hormone in a poloxamer hydrogel scaffold combined with a mixture of β‐tricalcium phosphate and hydroxyapatite (CP) may serve as a suitable bone graft. The aim of this study was to design and test a novel thermosensitive hydrogel graft incorporating oxytocin‐loaded poly(d, l‐lactide‐co‐glycolide) (PLGA) sustained‐release microspheres and CP. Thermosensitive poloxamer hydrogel containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The systemic administration of OT promotes peri-implant bone healing and osseointegration of titanium implant in ovariectomized rats, increasing bone volume and improving trabecular micro-structure surrounding the implant [24]. Furthermore, Aykay AS et al showed, in a rat model, that a thermosensitive hydrogel graft incorporating OT-loaded PGLA microspheres provides an accelerated bone regeneration in the rat calvaria [25].…”
Section: Ot and Bone Microarchitecturementioning
confidence: 99%
“…The systemic administration of OT promotes peri-implant bone healing and osseointegration of titanium implant in ovariectomized rats, increasing bone volume and improving trabecular micro-structure surrounding the implant [24]. Furthermore, Aykay AS et al showed, in a rat model, that a thermosensitive hydrogel graft incorporating OT-loaded PGLA microspheres provides an accelerated bone regeneration in the rat calvaria [25].…”
Section: Ot and Bone Microarchitecturementioning
confidence: 99%
“…Among the polymeric carriers for oxytocin, solvent displacement method was utilized to synthesize poloxamer hydrogel scaffold, to encapsulate oxytocin in hydrogel graft constituted of poly(d, l-lactide-co-glycolide) (PLGA), β-tricalcium phosphate, and hydroxyapatite (CP). This method yielded 89.5% encapsulation efficiency, slowly release encapsulated oxytocin, and finally yielded significant regeneration of bone loss in rat calvaria [35].…”
Section: Nano Micro and Macro Materials For Delivery Of Agonists And Antagonistsmentioning
confidence: 93%
“…Thanks to their unique features, poly (D, Llactide coglycolide) PLGA copolymers have been used as local drug carrier for different types of biomolecules [ 96 ]. Sustained release micro spherical oxytocin hormone in a polymeric hydrogel scaffold mixed with biphasic calcium phosphates combination promotes bone repair in the rat calvarias [ 97 ]. Furthermore, OT-loaded b-TCP increases osteogenesis in rats with calvarias bone defects via an osteoinductive mechanism of action [ 77 ].…”
Section: Examples Of Repositioned Hormones For Bone and Periodontal T...mentioning
confidence: 99%